Innovation in Teaching and Learning of Surveying and Mapping Course Based on Information and Technology (IT) - *, Sukatiman; Nugroho, Ida (Sebelas Maret University, 2016)
Learning based on Information and Technology in Surveying and Mapping (SM) course is urgently applicationÂ on vocational education in Indonesian in order to graduate can compete to global markets especially deal withÂ ASEAN Economic Community (AEC) 2015. This paper used action research method with 60 samples students inÂ class SM, while data collected was qualitative descriptive to understand studentâs achievement. To ensure thatÂ teaching aids based on IT whether has strong impacted during learning practice, the students gift feedback it wasÂ conducted by questionnaires. Learning strategy was performed in three phased, 1) learning preparation inÂ teaching aids ( used of module, TS teodholite equipment, and GPS handheld apparatus) , 2) learning practiceÂ conducted by Problem Based Learning (PBL), and 3) evaluation used authentic assessment. The result of theÂ research were 1) 97% students passed and just 3% still needs treatment, 2) the statistic computation use doubleÂ linear regression showed 3 indicators about normal distribution, correlation, and significantly, and its can beÂ conclusion that teaching aids based on IT has strong impacted to student achievement in learning practice SMÂ course.